BASILOXYLON K. Schumann and PTERYGOTA ENDL. (Stercul.) - A.J.G.H KOSTERMANS (REINWARDTIA, 1961)
In Martius, Fl. Brasil. 12 (3): 12. 1886 (in observ.) K. Schumann described a specimen (Peckolt 628) collected in Cantagallo (Rio de Janeiro), conserved in the Brussels Herbarium and marked by Martius Sterculia rex (after the local name Pao del Rey); he suggested to name it Basiloxylon rex, if it should prove to be new; the name is consequently not valid under the Rules, but it was validated by Schumann in the same year (in Berichte deutsche bot. Gesellsch. 4: 82, t. 3. 1886). The latter description was based partly on the specimen Glaziou 10310.